Meningkatkan Hasil Belajar Materi Gaya Dan Gerak menggunakan Model CAI (Computer Assisted Instruction) - Radiansyah, Radiansyah; Islami, Alfina Nur (Patria Artha Technological Journal, 2022)
The problem of this research is the low learning outcomes of learners in the IPA content of force and motion materials. The author uses the CAI model as a solution to overcome the problems that occur. This research aims to describe educator activities, student activities and analyze student learning outcomes in style and motion materials in class IV of SDN Pekauman 1 Banjarmasin. This research uses a qualitative approach with a type of PTK research consisting of 4 stages, namely: planning, implementation, observation and reflection, and using two types of data, namely qualitative data and quantitative data. The data was analyzed from the results of observations and learning evaluation tests in class IV students of SDN Pekauman 1 Banjarmasin for the 2020/2021 school year with a total of 8 students. The results showed that the application of the Computer Assisted Instruction (CAI) learning model of educator activity can be carried out very well, student activities achieve very active criteria and learning outcomes achieve completion